KONSEP TADABBUR AL-QUR’AN PERSPEKTIF KH. BACHTIAR NASIR - Suhartawan, Budi (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Al-Qur'an is the best reading of all time which if read will get guidance from Allah subhanahu wa ta'ala when interacting and as for how to interact with the Qur'an is the tadabbur method. This study aims to examine and test the concept of Tadabbur Al-Qur'an presented by KH. Bachtiar Nasir. To answer the social phenomena that are developing at this time. This research is included in the category of literature review with descriptive analysis techniques. The results of this research show that what is offered by KH. Bachtiar Nasir can be accepted by all groups. Because the method offered by him is very easy and aflikatif.